Minimum Cost Multiobjective Programming Model for Target Efficiency in Sample Selection - Shamsuddin, Sadaf; Shoukry, Alaa Mohamd; Hussain, Ijaz; Khan, Saima; Shad, Muhammad Yousaf; Hussain Gani, Showkat (Scientific programming, 2019)
In this study, we developed a model which elaborates relationship among efficiency of an estimator and survey cost. This model is based on a multiobjective optimization programming structure. Survey cost and efficiency of related estimator(s) lie in different directions, i.e., if one increases, the other decreases. The model presented in this study computes cost for a desired level of efficiency on various characteristics (goals). The calibrated model minimizes the cost for the compromise optimal sample selection from different strata when characteristic j is subject to achieve at least 1−αj level of efficiency of its estimator. In the first step, the proposed model minimizes the variance for a fixed cost, and it then finds the rise in cost for an αj percent rise in efficiency of any characteristic j. The resultant model is a multiobjective compromise allocation goal programming model.